2010
DOI: 10.1007/s13277-010-0145-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and prognostic analysis of gastric cancer in the young adult in China

Abstract: The incidence of gastric cancer in young has increased steadily in the last decades. Little is known about the clinicopathologic features and prognostic factors of young adult gastric cancer patients. The clinicopathological characteristics of 294 young adult gastric cancer patients between 20 and 50 years old were reviewed retrospectively from hospital records in Sun Yat-Sen University Cancer Center between 1996 and 2006. They were compared with 706 elder patients 51 years of age or over. A steady increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 23 publications
6
30
1
Order By: Relevance
“…In our previous study, we showed that as the age increased there was a steady increasing in the proportion of male and steady decreasing of female [24]. Similarly, we presently also found a steady increasing in the ratio between male and female as the age increased.…”
Section: Discussionsupporting
confidence: 71%
“…In our previous study, we showed that as the age increased there was a steady increasing in the proportion of male and steady decreasing of female [24]. Similarly, we presently also found a steady increasing in the ratio between male and female as the age increased.…”
Section: Discussionsupporting
confidence: 71%
“…Other authors have obtained different results, so that gastric cancer in younger patients has been commonly considered more aggressive and as having a poorer prognosis [57, 22]. Conversely, other researchers have reported better long-term survival outcomes in younger age groups [7, 16, 17, 23]. A recent investigation conducted on 2,757 patients younger than 45 showed that younger age was associated with improved survival after stratification by cancer stage at presentation, suggesting that a stage-dependent rather than age-dependent approach should be taken in younger patients with gastric cancer [5].…”
Section: Discussionmentioning
confidence: 99%
“…Qiu et al . [6] reported that the MFSR increased with an increase in age. The total MFSR was 2.15:1.…”
Section: Introductionmentioning
confidence: 99%